THE INFLUENCE OF BRAND IMAGE AND BRAND AMBASSADORS ON PURCHASE DECISIONS FOR SOMETHINC PRODUCTS IN TIKTOK SHOP - Aninda Fitri Litasni; Adelia Riana Dewi (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to determine the effects of brand image and brand ambassador on purchase decisions for Somethinc products on TikTok Shop, both partially and simultaneously. This study employed a quantitative approach using primary data. The stages of analysis included validity, reliability, normality, multicollinearity, and heteroscedasticity tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The study involved 100 respondents. A non-probability sampling method with a purposive sampling technique was used to select the sample. SPSS 27 was used as the analytical tool. The t-test results show that brand image has a positive effect on purchase decisions and that brand ambassador also has a positive effect on purchase decisions. Meanwhile, the F-test results show that brand image and brand ambassador simultaneously affect purchase decisions for Somethinc products on TikTok Shop.